Substrate specificity of angular dioxygenase from carbazole-degrading bacterium Neptuniibacter sp. strain CAR-SF - Azizah, Ahmad; Azham, Zulkharnain; Awang Ahmad Sallehin, Awang Husaini (International Journal of chemical and pharmaceutical sciences, 2015)
Carbazole-degrading bacteria have been shown to have broad substrate specificity towards various contaminants. Carbazole 1,9a-dioxygenase (CARDO) from Neptuniibacter sp. strain CAR-SF composed of terminal oxygenase component CarAa, ferredoxin component CarAc, and ferredoxinreductase component CarAd.Expression vector encoding carbazole 1,9a-dioxygenase (CARDO) from Neptuniibacter sp. strain CAR-SF CARDO, pETCARA1 was constructed and dioxygenase activity was assessed by monitoring the blue-indigo production in Luria broth media and SDS-PAGE. Gas chromatography-mass spectrometry analysis revealed the angular dioxygenation of dibenzofuran at angular position adjacent to oxygen atom to yield 2,2’,3- Trihydroxybiphenyl. CARDO also demonstrated activity towards dibenzothiophene and fluorene by converting the substrates into monooxygenation products, dibenzothiophene-5-oxide and 9-Fluorenone respectively. Cisdihydrodiols and monohydroxylated products were also seen in the biotransformation of naphthalene, biphenyl and fluoranthene. These diverse oxygenations illustrated by CARDO revealed the broad versatility in its action on polyaromatic compounds and thus will make it as an excellent tool for bioremediation application.